Update on Idiopathic Intracranial Hypertension Management - Marcio Nattan Portes Souza; Barbara de Alencar Leite Costa; Felipe Reinaldo Deus Ramos Santos; Ida Fortini (Arquivos de Neuro-Psiquiatria, 2022)
ABSTRACT Background: Idiopathic Intracranial Hypertension (IIH) is a secondary headache with a steadily growing incidence. Currently, there is little evidence to guide the treatment of IIH. Objective: To review the pathophysiology of IIH, with focus on the role of obesity as a risk factor, and the implications for new therapeutic perspectives. Methods: in this narrative review, we summarized the current knowledge on treatment options highlighting available evidence for managing intracranial hypertension, obesity, and headache. Results: Clinical Presentation: headache is the most common symptom and a significant cause of quality-of-life impairment. Visual loss is common in the diagnosis. Pathophysiology: there is no unified theory able to explain all symptoms and the evolution of the disease. There is growing data pointing to metabolic changes and obesity with a central role in IIH pathophysiology. Treatment: most published data on IIH treatment is related to pressure control and protection from visual loss. Acetazolamide and cerebrospinal fluid diversion are the best options available. Optic nerve sheath fenestration might be useful to temporally control the pressure over the optic nerve and thus protect from visual deterioration. Recently, venous sinus stenting has proven to be a safe option in selected cases. Finally, bariatric surgery has proven to effectively control elevated intracranial pressure. Conclusion: IIH is a potential cause of high disability. Early recognition is important, and treatment should be tailored to the needs of each case. There is a lack of research on headache management, which might persist after ICP control.